Globalization and its Impact on Small Scale Industries-An Analysis - Masood, Rana Zehra (Indian Journal of Marketing, 2009)
SSI is widely recognized as a powerful instrument for socio-economic growth and balanced sectorial development. One of the distinctive characteristics of the SSI sector is its capacity to create broader employment opportunities, assist in entrepreneurship and skills development and ensure better use of scarce financial resources and appropriate technology. The Indian National Congress took over the reins of power after India’s Independence in 1947. Most of the Congress leaders came to occupy responsible positions in the Central and State Governments. It was, therefore, expected that the sanctity bestowed on Khadi and village industries by Gandhi would be preserved and adopted unhesitatingly as a national and public policy in free India. It was also expected that the ideals of building self-reliant villages was a commitment that had to be discharged faithfully by the party and the followers of Gandhiji. Because of the then prevailing political environment, especially the place and the role Gandhiji played in the struggle for independence, there was no serious debate on or critical scrutiny of the issues Gandhiji was associated with and had expressed his clear views. There were, however, many who were extremely critical of the Gandhian philosophy for socio-economic development of the country.